Ctrophotometyric Determination of Heavy Metal (Lead) in Cosmetics (Lipsticks) in Commercial Markets - Adil Mohammed Hashim 1 , Ali Mohammed Abd-Alameer 1 , Ahmed Hameed Rashed1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the recent years an significant rise were occurred due to exposure human being of heavy metal . There areno escaping from exposure to toxic chemical and heavy metal . The aim of this study was to determine andevaluate the risk heavy metal in lipstick on the public health, so we selected one heavy metal (lead) in therandomly selected lipstick samples from local markets . We determine lead in 28 lipstick products samples.Cosmetic products have a wide number of forms and uses ,many of them contain chemical compoundsthat may passé through the skin. High concentration of heavy metal in lipsticks which could form potentialhealth risk on public health , especially we know this lead accumulate in biological system . we used todetermine lead spectrophotometer technique . The samples were analyzed based on international standardby using (HNO3 ; H2O2) method . The concentration of maximum lead in random samples was (1.4) ppm, while the minimum lead was (0.02)ppm .This results were below the recommended limits of the unitedstate Food and Drug Administration .In manufacturing of lipsticks must be monitoring the componentsand chemicals used . Also quality control take place to check the concentration of heavy metal in lipstickproducts in each country .